Waste of molded pulp industry. Filler panel production for construction - Andrés, Federico (2015)
In the production process for producing recycled pulp cellulose, there are waste generated by the raw material entering the system. This residue is separated from the pulp by physical methods, and is mainly composed of plastics, paper, laminated papers and other materials in smaller proportions. In order to recycle this waste, in this paper we analyze the viability of use in the production of insulated panels. With the untreated residue extracted from the plant, panels of 30 cm side and thickness of approximately 6 cm were made. On these panels, parameters such as density and compression strength were evaluated for the study of the homogeneity of the material obtained